The Relationship Between Cancer and Functional and Structural Markers of Subclinical Atherosclerosis: A Systematic Review and Meta-Analysis - Diao, Yuhong; Liu, Zhixing; Chen, Li; Zhang, Weiping; Sun, Dandan (Frontiers in Cardiovascular Medicine, 2022)
Objectives The relationship between cancer and subclinical atherosclerosis has always been the focus of people's attention. We conducted a systematic review and meta-analysis by evaluating the effects of cancer on functional and structural markers of subclinical atherosclerosis:intima-media thickness (IMT), pulse wave velocity (PWV), and flow-mediated vasodilation (FMD). Methods A comprehensive and systematic literature search was conducted on the internet. Sensitivity analysis, publication bias, standard mean difference (SMD), corresponding 95% confidence interval (95% CI), and subgroup analysis were performed for all relevant research indicators in the retrieved literature. Results Forty-six studies were included, including 3,729 cancer patients and 2,404 healthy controls. Cancer patients had significantly thicker IMT [SMD (95%CI) = 0.290 (0.069 to 0.511), P = 0.010] and higher PWV [SMD (95%CI) = 0.392 (0.136 to 0.647), P = 0.003] compared with healthy controls. There was no significant difference in FMD [SMD (95% CI) = −0.192 (−0.527 to 0.144), P > 0.05). After subgrouping by age, male proportion, and treatment, the analysis results of IMT ≥ 50 years old, PWV and FMD < 50 years old, male proportion ≥50%, chemotherapy group, IMT and PWV radiotherapy group, and PWV endocrine therapy group were statistically significant (P < 0.05). There were no significant differences in other subgroup analyses, overall sensitivity analysis, and publication bias (p < 0.05). Conclusions Cancer may promote subclinical atherosclerosis, and change the functional and structural markers of subclinical atherosclerosis such as IMT and PWV. Early intervention and prevention should be pursued.